International compendium of coastal engineering - Satō, Shinji; Isobe, Masahiko (World Scientific, 2015)
"The aim of this book is to provide a comprehensive overview of Coastal Engineering from basic theory to engineering practice. The authors of this book are worldwide authorities in the field. Each chapter deals with an important topic in the field of coastal engineering. The topics are of recent deep concern all over the world motivated by the 2004 Indian Ocean Tsunami, 2005 Hurricane Katrina, 2011 Tohoku Earthquake Tsunami and other natural disasters. For proper coastal zone management, a broad range of knowledge is necessary. This book provides a basic understanding of the theories behind the diverse natural phenomena within the coastal areas, such as waves, tsunamis and sediment transport. The book also introduces various coastal conservation technologies such as coastal structures and beach nourishment. Finally, coastal zone management practices in the USA, Europe, and Japan are introduced. Each chapter is self-standing and readers can begin from any topic depending on their interest."--